Pengembangan Aplikasi Mobile untuk Pembukuan dan Kasir Usaha Laundry dengan Metode User-Centered Design - Ricky Reza Ananda; Syarif Hidayat (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Laundromat is a general business that can be found around where we live, this kind of business is also part of micro, small and medium enterprise. On the operation of a business should include a bookkeeping process that usefull for monitoring financial flow from the business itself. As the technology advances, the bookkeeping process can be done within our smartphone. Therefore the goal of this study is to make a mobile application called LaPlus for the bookkeeping process and also include POS system. User centered design is a method that will be used on this study because the users is our main focus to make a good application that satisfy the users need. With the result of 89% success rate on the usability testing its shows the product design is easily understood and accepted by its users.